Professional Discourse: An Editorial Comment - McGuire, Richard (My University, 1987)
McGuire took over as editor from Gerry Gurney. He indicated that starting in Fall 1987, short pieces on topics relevant to the profession may be included in the journal issues. He also proposed some of his own ideas that deviate from rules changes regarding printed materials for prospective athletes and initial eligibility regulations.
Keywords: editorial